Low Altitude Solar Magnetic Reconnection, Type III Solar Radio Bursts, and X-ray Emissions - Cairns, I.; Lobzin, V.; Donea, A.; Tingay, Steven; McCauley, P.; Oberoi, D.; Duffin, R.; Reiner, M.; Hurley-Walker, Natasha; Kudryavtseva, N.; Melrose, D.; Harding, J.; et al. (Nature Publishing Group, 2018)
Type III solar radio bursts are the Sun's most intense and frequent nonthermal radio emissions. They involve two critical problems in astrophysics, plasma physics, and space physics: how collective processes produce nonthermal radiation and how magnetic reconnection occurs and changes magnetic energy into kinetic energy. Here magnetic reconnection events are identified definitively in Solar Dynamics Observatory UV-EUV data, with strong upward and downward pairs of jets, current sheets, and cusp-like geometries on top of time-varying magnetic loops, and strong outflows along pairs of open magnetic field lines. Type III bursts imaged by the Murchison Widefield Array and detected by the Learmonth radiospectrograph and STEREO B spacecraft are demonstrated to be in very good temporal and spatial coincidence with specific reconnection events and with bursts of X-rays detected by the RHESSI spacecraft. The reconnection sites are low, near heights of 5-10 Mm. These images and event timings provide the long-desired direct evidence that semi-relativistic electrons energized in magnetic reconnection regions produce type III radio bursts. Not all the observed reconnection events produce X-ray events or coronal or interplanetary type III bursts; thus different special conditions exist for electrons leaving reconnection regions to produce observable radio, EUV, UV, and X-ray bursts.